Особливості впливу пожеж на фітогенні форми рельєфу в межах басейну річки Остер - Філоненко, Ю. М. (Київський національний університет імені Тараса Шевченка, 2025)
Вивчення впливу полум’я на стан та особливості еволюції фітогенних форм рельєфу в межах території басейн річки річки Остер є важливим і актуальним. Такі форми рельєфу, у більшості своїй, представлені в місцях (заплави річок; болотні комплекси; ліси та узлісся; захисні лісові смуги вздовж залізниць, автомобільних доріг, річок, на полях та по периметру водойм; території парків тощо) де ймовірність пожеж в останні роки є досить високою. Під впливом вогню зовнішній вигляд фітогенних форм рельєфу, їх розміри, характер поверхні і речовинний склад зазнають суттєвих змін, а найдрібніші з них зникають взагалі. Дослідження впливу пожеж на фітогенний рельєф дає можливість оцінити роль та масштаби впливу пірогенного чинника у фітогенному рельєфотворенні. Враховуючи інформацію, наявну в публікаціях відомих дослідників, та спираючись на результати власних польових досліджень, було проаналізовано особливості впливу пожеж на фітогенні форми рельєфу в межах басейну річки Остер. Зокрема, було досліджено болотні комплекси та заболочені території, які є найбільшими формами фітогенного рельєфу, поверхня яких зазнає значних змін внаслідок пірогенного впливу. Встановлено, що під дією полум’я суттєво зменшуються розміри та змінюється зовнішній вигляд купин, а також відбувається ущільнення мертвої фітомаси, яка їх складає. Було визначено, що внаслідок пожеж відбувається значна деформація пристовбурових піднять, вітровальних горбів, ям і мікропасм, а також звивистих мікропасм утворених кореневими системами дерев. Варто також зазначити, що дернові і мохові горбочки та мікропасма і очеретяні береги водойм та водотоків найчастіше знищуються під впливом полум’я повністю, а внаслідок підземних пожеж на багатьох ділянках боліт має місце просідання поверхні, яке призводитть до утворення улоговин різного розміру та обрисів.

T he study of the impact of flame on the state and features of the evolution of phytogenic landforms within the territory of the Oster River basin is important and relevant. Such landforms are mostly represented in places (river floodplains, swamp complexes, forests and forest edges, protective forest belts along railways, highways, rivers, fields and the perimeter of water bodies, park territories, etc.) where the probability of fires in recent years has been quite high. Fires in the studied area occur most often in spring and autumn. Their main cause is the human factor, namely deliberate arson, failure to comply with fire safety rules when making bonfires in the countryside, burning plant remnants on agricultural lands and in private households, spontaneous combustion of garbage at illegal dumps, discarded cigarette butts, children's mischief with fire, enemy shelling, etc. Under the influence of fire, the appearance of phytogenic landforms, their size, surface character, and material composition undergo significant changes, and the smallest of them disappear altogether. The study of the influence of fire on phytogenic landforms makes it possible to assess the role and scale of the influence of the pyrogenic factor in phytogenic landform formation. Taking into account the information available in the publications of well-known researchers and based on the results of our own field research, the specifics of the impact of fires on phytogenic landforms within the Oster River basin were analyzed. In particular, swamp complexes and wetlands were studied, which are the largest forms of phytogenic relief, the surface of which undergoes significant changes due to pyrogenic impact. It was established that under the influence of flame, the mounds significantly reduce in size and their appearance changes as well as the dead phytomass that makes them up is compacted. It was determined that fires cause significant deformation of trunk ridges, wind humps, pits, and micro-strips as well as winding micro-strips formed by tree root systems. It is also worth noting that turf and moss mounds, micro-strips, and reedy banks of water bodies and watercourses are most often completely destroyed under the influence of fire. Meanwhile, as a result of underground fires, in many areas of the swamps surface subsidence occurs, which leads to the formation of depressions of various sizes and shapes.
Features of the impact of fires on phytogenic landforms within the Oster River basin
Keywords: фітогенний рельєф; пожежа; болото; вітровальний горб; купина; вигорання; вітровальне пасмо; фітомаса; улоговина; пристовбуровий горб; phytogenic relief; fire; swamp; wind hump; mound; combustion; wind strip; phytomass; hollow; root crown